How Can We Address What We Do Not Measure? A Systematic Scoping Review of the Measurement and Operationalization of Social Determinants of Health Research on Long-Acting Reversible Contraceptive among Adolescents in the US - Catherine Poehling; Margaret Mary Downey; Anwei Polly Gwan; Sarah Cannady; Olivia Ismail (MDPI AG, 2023)
Teen pregnancy is often considered an adverse health outcome that accentuates gender inequities, diminishes opportunities, and jeopardizes the safety of adolescent and young adult birthing people. Long-Acting Reversible Contraceptives (LARC) have been hailed as a panacea for teen pregnancy. However, adolescents and emerging adults intersect with multiple assaults on their health and well-being due to gender inequity and racism. To establish equitable care, it is imperative to discern all barriers that influence their reproductive autonomy. This study evaluates the measurement, operationalization, and quality of research conducted on adolescents and emerging adults that analyzed the use of LARC within the social determinant of health framework (SDOH) in the US. SDOH were assessed using the Dahlgren and Whitehead model, and reports were analyzed using a modified version of the Joanna Briggs Institute (JBI) Critical Appraisal tools. Nineteen articles were included in this study. Researchers found the insufficient measurement of race, ethnicity, sexuality, and gender among studies on LARC and SDOH in adolescents and emerging adults. Future studies must measure a full range of identities in data collection to generate knowledge on the impact of SDOH and LARC use among diverse populations.